Sunday Service at Unitarian Universalist Church of Fresno - Watkins, Howard::::::::: (1988)
Children singing: Margaret Olmos, Vanessa Rhodes, Tara Boyd, ?,Marcy Spaulding, Leah Hanzlicek, and Juanita Temple; Paula Siegel seated and conducting on right side.